2019
DOI: 10.1111/epi.16295
|View full text |Cite
|
Sign up to set email alerts
|

EEG before and after total corpus callosotomy for pharmacoresistant infantile spasms: Fast oscillations and slow‐wave connectivity in hypsarrhythmia

Abstract: Objective We analyzed the features of fast oscillations (FOs) and connectivity in hypsarrhythmia to identify biomarkers for predicting seizure outcomes after total corpus callosotomy (TCC) in children with pharmacoresistant infantile spasms (IS). We hypothesize that the power of FOs and connectivity of slow waves in hypsarrhythmia would indicate the prognosis of IS. Method We retrospectively identified 42 children with pharmacoresistant IS who underwent TCC from 2009 to 2014 at Nagasaki Medical Center. We coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…After CC, the generalized discharges often disappear. In patients with hypsarrhythmia, which represents the most chaotic generalized/multifocal epileptic discharges, the interictal epileptiform discharges become either bilateral independent discharges or unilateral discharges, or none after CC (Baba et al 2019). In our present series, 5 patients required further VNS for their remaining generalized onset seizures.…”
Section: Bilateral Spreading After CC On Gmftmentioning
confidence: 67%
See 1 more Smart Citation
“…After CC, the generalized discharges often disappear. In patients with hypsarrhythmia, which represents the most chaotic generalized/multifocal epileptic discharges, the interictal epileptiform discharges become either bilateral independent discharges or unilateral discharges, or none after CC (Baba et al 2019). In our present series, 5 patients required further VNS for their remaining generalized onset seizures.…”
Section: Bilateral Spreading After CC On Gmftmentioning
confidence: 67%
“…CC is known to be effective for drop attacks caused by myoclonic, tonic, or atonic seizures (Tanriverdi et al 2009;Maehara and Shimizu 2001;Oguni et al 1991;Rossi et al 1996). In children with infantile spasms and hypsarrhythmia, the function of the corpus callosum in the chaotic bilateral fast and slow oscillations of hypsarrhythmia has been reported to be an essential part of the modulation of interhemispheric discharges (Baba et al 2019). In our present study, we evaluated patients for whom CC did not improve seizure control and further VNS was required.…”
Section: Corpus Callosotomy and Vagus Nerve Stimulationmentioning
confidence: 95%
“…Previous studies on the analysis of the EEG power indicated that the emergence of gamma activity during interictal scalp EEG in patients with West syndrome positively correlated with intractableness of seizures or severity of hypsarrhythmia (17,18). Moreover, abnormal EEGs, defined as abnormal backgrounds Although the mean CPS in each patient tended to be higher in unfavorable outcome group in all frequency bands, significant differences were seen in the delta, theta, and gamma bands.…”
Section: Relative Ps Analysesmentioning
confidence: 94%
“…Of these, three patients achieved seizure freedom with CC only, and two achieved seizure freedom through additional treatments [9]. In the patients with partial response in those previous studies, CC achieved reduction of seizure frequency and/or changed the ES into smaller ones, like head nodding or resolving drop attacks, unilaterally focal onset ES, or bilaterally independent focal onset-ES [3,4,6,[8][9][10][11][12]61,71]. Large data of long-term outcomes of CC for ES is unavailable.…”
Section: Seizure Outcomes Post-corpus Callosotomy For Epileptic Spasmsmentioning
confidence: 94%
“…In these cases, ictal EEG is visually bilateral and synchronous on slow waves [10]. Computed frequency analyses of presurgical scalp EEG recordings have shown small phase lags of ictal slow and beta waves among the bilateral hemispheres and less power and connectivity on interictal records [8,11]. caused predominantly by unilateral cortices and tend to show a uniformly lateralized seizure type.…”
Section: Types Of Epileptic Spasms In Terms Of Cortical Excitations and The Role Of Corpus Callosummentioning
confidence: 99%